Decadal changes in the chlorophyll seasonal cycles regional covariability with sea surface temperature and mixed layer depth - Martinez, E.; Antoine, David; d'Ortenzio, F.; de Boyer Montégut, C. (ASLO Aquatice Sciences, 2009)
A reprocessing of the CZCS and SeaWiFS data sets was previously performed (Antoine et al., 2005) to investigate the decadal changes in the global ocean chlorophyll (Chl). This global reanalysis showed an average increase of Chl by ~20%. Then, the spatial and temporal covariability between Chl and Sea Surface Temperature (SST) was investigated although limited to the Non Seasonal signal to better highlight the long-term variability (Martinez et al., in prep). A Chl-SST inverse relationship was frequently observed, and decadal changes essentially result from basin-scale low-frequency natural oscillations. Because Chl decadal changes were not fully explained by the Non Seasonal signal, the objective is now to investigate the seasonal cycle. The time downscaling of this work requires a sufficient temporal coverage of the considered parameters. Regional studies are necessary and performed where data are the most available, i.e. in the northern hemisphere. SST and Chl satellite data are completed with in situ temperature and derived mixed layer depth by de Boyer Montégut et al. (2004) to explicitly investigate the role of the oceanic stratification in the observed Chl changes.